An exploratory randomized controlled trial comparing wood-composite and synthetic fibreglass splint systems for the immobilization of paediatric upper limb fractures. (3rd October 2020) - Martynov, Illya; Klink, Thomas; Slowik, Volker; Stich, Rainer; Zimmermann, Peter; Engel, Christoph; Lacher, Martin; Boehm, Roland
Abstract : Aims: This exploratory randomized controlled trial (RCT) aimed to determine the splint-related outcomes when using the novel biodegradable wood-composite splint (Woodcast) compared to standard synthetic fibreglass (Dynacast) for the immobilization of undisplaced upper limb fractures in children. Methods: An exploratory RCT was performed at a tertiary paediatric referral hospital between 1 June 2018 and 30 September 2019. The intention-to-treat population consisted of 170 patients (mean age 8.42 years (SD 3.42); Woodcast (WCG), n = 84, 57 male (67.9%); Dynacast (DNG), n = 86, 58 male (67.4%)). Patients with undisplaced upper limb fractures were randomly assigned to WCG or DNG treatment groups. Primary outcome was the stress stability of the splint material, defined as absence of any deformations or fractures within the splint during study period. Secondary outcomes included patient satisfaction and medical staff opinion. Additionally, biomechanical and chemical analysis of the splint samples was carried out. Results: Of the initial 170 patients, 168 (98.8%) completed at least one follow-up, and were included for analysis of the primary endpoint. Both treatment groups were well-matched regarding to age, sex, and type and localization of the fracture. Splint breakage occurred in three patients (3.6%; 95% confidence interval (CI), 0.007% to 0.102%) in the WCG and in three children (3.5%, 95% CI 0.007% to 0.09%) in the DNG (p > 0.99). The incidence of splint-related adverse events did not differ between the WCG (n = 21; 25.0%) and DNG (n = 24; 27.9%; p = 0.720). Under experimental conditions, the maximal tensile strength of Dynacast samples was higher than those deriving from Woodcast (mean 15.37 N/mm² (SD 1.37) vs 10.75 N/mm² (SD 1.20); p = 0.002). Chemical analysis revealed detection of polyisocyanate-prepolymer in Dynacast and polyester in Woodcast samples. Conclusion: Splint-related adverse events appear similar between WCG and DNG treatment groups during the treatment of undisplaced forearm fractures. Cite this article: Bone Joint J 2020;102-B(10):1405–1411.